Perseverence: A Positive Attitude that will Make You Succeed in Life - Gonzalez, Cristo (CIEX JOURNAL, 2019)
The term perseverance is related to understanding yourself, setting goals, and planning, but action is required to make your dreams come true. In order for you to control of your life it is necessary to choose and make the correct decisions and put them into action. Perseverant people belief know that they have control over important aspects of their lives. Confidence in one’s own capacities or skills that will make it easy to succeed in any kind of activity. (Mary Pickford).